Role of Frugivorous Birds in Seed Dispersal in the Mixed Dry Deciduous forests of Attappady and Anaikatty, Western Ghats - Aruna, R.; Balasubramanian, P.; Radhakrishnan, P. (Indian Forester, 2009)
The Attappady Hills Area Development Society (AHADS) as part of eco-restoration programmes in Attappady hills, Western Ghats, initiated tree planting programmes to identify the bird-attracting species. Study sites were chosen in the degraded dry deciduous forests of Attappady and the adjoining Anaikatty reserve forests representing the mixed dry deciduous forest. Frugivorous birds were ascertained by making extended feeding watches on fleshyfruited plant species and bird counts along transects. Twenty nine bird species were observed to eat fruits. Among the frugivore visitors, bulbuls (5 species) made highest number of feeding visits (45%), followed by mynas, 2 species (16%), babblers, 3 species (14.5%) and others. A total of 40 bird-attracting species were recorded in the study area. Moraceae represented by six species was found to be the most dominant bird-attracting family followed by Rutaceae and Euphorbiaceae. Among the 40 species, Ficus benghalensis attracted maximum number of avian frugivores followed by Ficus microcarpa, Benkara malabarica, Cassine glauca and Canthium dicoccum. A suggestion is made to plant the bird-attracting native species in the degraded sites of Attappady.